Cannabinoid receptor type 1 in the bed nucleus of the stria terminalis modulates cardiovascular responses to stress via local N-methyl-D-aspartate receptor/neuronal nitric oxide synthase/soluble guanylate cyclase/protein kinase G signaling - Gomes-de-Souza, Lucas [UNESP]; Costa-Ferreira, Willian [UNESP]; Oliveira, Leandro A [UNESP]; Benini, Ricardo [UNESP]; Crestani, Carlos C [UNESP] (SAGE Publications, 2020)
Background: Endocannabinoid neurotransmission in the bed nucleus of the stria terminalis is involved in the control of cardiovascular responses to stress. However, the local mechanisms involved is this regulation are not known. Aims: The purpose of this study was to assess an interaction of bed nucleus of the stria terminalis endocannabinoid neurotransmission with local nitrergic signaling, as well as to investigate the involvement of local N-methyl-D-aspartate glutamate receptor and nitric oxide signaling in the control of cardiovascular responses to acute restraint stress by bed nucleus of the stria terminalis endocannabinoid neurotransmission in rats. Methods: The first protocol evaluated the effect of intra-bed nucleus of the stria terminalis microinjection of the selective cannabinoid receptor type 1 receptor antagonist AM251 in nitrite/nitrate content in the bed nucleus of the stria terminalis following restraint stress. The other protocols evaluated the impact of local pretreatment with the selective N-methyl-D-aspartate glutamate receptor antagonist LY235959, the selective neuronal nitric oxide synthase inhibitor Nω-propyl-L-arginine, the soluble guanylate cyclase inhibitor 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one, or the protein kinase G inhibitor KT5823 in restraint-evoked cardiovascular changes following bed nucleus of the stria terminalis treatment with AM251. Results: Bilateral microinjection of AM251 into the bed nucleus of the stria terminalis increased local nitric oxide release during restraint stress. Bed nucleus of the stria terminalis treatment with the cannabinoid receptor type 1 receptor antagonist also enhanced the tachycardia caused by restraint stress, but without affecting arterial pressure increase and sympathetic-mediated cutaneous vasoconstriction. The facilitation of restraint-evoked tachycardia following bed nucleus of the stria terminalis treatment with the cannabinoid receptor type 1 receptor antagonist was completely inhibited by local pretreatment with LY235959, Nω-propyl-L-arginine, 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one, or KT5823. Conclusions: Our results provide evidence that bed nucleus of the stria terminalis endocannabinoid neurotransmission inhibits local N-methyl-D-aspartate/neuronal nitric oxide synthase/soluble guanylate cyclase/protein kinase G signaling, and this mechanism is involved in the control of the cardiovascular responses to stress.
Keywords: bed nucleus of the stria terminalis; endocannabinoid; glutamate; nitric oxide; Restraint